Estudo da mecânica da danificação aplicada ao concreto com efeitos de corrosão - Codes, Rodrigo Nogueira de (2006)
Damage and failure of concrete are widely investigated in the framework of continuum damage mechanics. Various models exist in the literature and describe quite well a variety of observed phenomena depending on their complexity. The main objective of the work is to investigate and model the effects of corrosion on damage and failure properties of concrete. Initially, we made tests of traction and compression in some specimens of concrete, some of them submitted to the corrosion in a salt spray chamber (with different periods of time) and others without any corrosion, to determine the mechanical behaviour of the concrete taking itself in consideration the effect of the corrosion. For the traction test, we developed a device composed of steel parts, where, with this test, we can obtain the stress strain curve using the same specimens in traction and in compression. With these experimental results, using the Continuum Damage Mechanics, an elastic model coupled to damage was used to model the behaviour of the concrete. A first stage, isotropic elasticity and isotropic damage (with only one scalar variable D) was used, but including corrosion effects. With the results, we can analyze the evolution of damage in the concrete with relation to the time of exposition of the specimens in the salt spray chamber and function of the mechanical loading.